Vat polymerization-based bioprinting - process, materials, applications and regulatory challenges - Ng, Wei Long (2020)
Over the years, the field of bioprinting has attracted attention for its highly automated fabrication system that enables the precise patterning of living cells and biomaterials at pre-defined positions for enhanced cell-matrix and cell-cell interactions. Notably, vat polymerization (VP)-based bioprinting is an emerging bioprinting technique for various tissue engineering applications due to its high fabrication accuracy. Particularly, different photo-initiators (PIs) are utilized during the bioprinting process to facilitate the crosslinking mechanism for fabrication of high-resolution complex tissue constructs. The advancements in VP-based printing have led to a paradigm shift in fabrication of tissue constructs from cell-seeding of tissue scaffolds (non-biocompatible fabrication process) to direct bioprinting of cell-laden tissue constructs (biocompatible fabrication process). This paper, presenting a first-time comprehensive review of the VP-based bioprinting process, provides an in-depth analysis and comparison of the various biocompatible PIs and highlights the important considerations and bioprinting requirements. This review paper reports a detailed analysis of its printing process and the influence of light-based curing modality and PIs on living cells. Lastly, this review also highlights the significance of VP-based bioprinting, the regulatory challenges and presents future directions to transform the VP-based printing technology into imperative tools in the field of tissue engineering and regenerative medicine. The readers will be informed on the current limitations and achievements of the VP-based bioprinting techniques. Notably, the readers will realize the importance and value of highly-automated platforms for tissue engineering applications and be able to develop objective viewpoints towards this field.